Housing stock study: demand and supply in Perak - Mohamed Osman, Mariana; Bachok, Syahriah; Abdullah, Alias; Abdul Rashid, Khairuddin; Shuid, Syafiee; Abdullah, Muhammad Faris (2016)
The housing supply and demand study will provide the evidence to validate the housing supply targets as defined in local plan and the state structure plan. The projections and forecasts of the housing supply and demand will address the future housing need and demand based on development plans particularly for Perak State development. A regular, five-yearly review of the assessment is needed to link the local housing demand and supply with the development plan strategies which will provide an opportunity to ensure the maintenance of an appropriate long term approach. The housing supply and demand assessments are important in assisting the state and local authority policy on housing development, decision-making and resource-allocation processes.